2015
DOI: 10.1080/21681015.2015.1029549
|View full text |Cite
|
Sign up to set email alerts
|

Hub-and-spoke airline network design under competitive market

Abstract: This study proposed a hub-and-spoke network design model with the uncertainty of a competitor's information in a duopolistic airline market. The market share is affected by the prices of both players in the market and the prices are assumed to be proportional to their transportation costs. The source of uncertainty in the problem is due to the imperfect information on the competitor's price setting. The stochastic programming was applied to formulate the system randomness. An illustrative example from air frei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…For the problem of considering both service pricing and pivot point selection in a competitive environment, scholars mainly divided the research on customer demand distribution into the following aspects: path cost [29][30][31][32], price [23,[33][34][35], cost and price [14,16], route cost and transportation time [36][37][38][39][40], cost and service [41,42]. Through the review, it is found that few literature consider both cost and price factors, and the previous studies mostly take distance, cost, and time as the basic parameters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the problem of considering both service pricing and pivot point selection in a competitive environment, scholars mainly divided the research on customer demand distribution into the following aspects: path cost [29][30][31][32], price [23,[33][34][35], cost and price [14,16], route cost and transportation time [36][37][38][39][40], cost and service [41,42]. Through the review, it is found that few literature consider both cost and price factors, and the previous studies mostly take distance, cost, and time as the basic parameters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It also gathers logistics demands [13]. The research of huband-spoke network model focuses on the selection of nonhub node assignment [14], the cost discount rate setting between hub nodes [15], the connection constraint between nonhub nodes [16], and the multilevel [17]. At present, the hub-and-spoke network model has been described integrally [18], and it has begun to expand into new research directions in combination with applications in different fields.…”
Section: State Of the Artmentioning
confidence: 99%
“…For example, a hybrid hub-and-spoke postal logistics network was studied by LEE, and Moon [19]. The hub-and-spoke route network in the competitive market was studied by Yang, and Huang [20], and the secondary diffusion of Marine species introduced in Indonesia using hub-and-spoke networks was studied by Azmi, Hewitt, and Campbell [21]. However, applying the design of the hub-and-spoke network to the network planning field of URL is a relatively new idea.…”
Section: State Of the Artmentioning
confidence: 99%